Gastrointestinal Stromal Tumor of the Rectovaginal Septum, a Diagnosis Challenge - Sanmartin, Josefa Marcos; Sanchez, Maria Jose Roman; Fernandez, Jose Antonio Lopez; Sanchez, Óscar Pinero; Hidalgo, Amparo Candela; Galiana, Hortensia Ballester; Fuster, Natalia Esteve; Lopez, Aranzazu Saco; Escoriza, Juan Carlos Martínez (IntechOpen, 2012)
None